Kathleen Adler & Marcia Pointon (eds.): The Body Imaged: The Human Form and Visual Culture in the Renaissance - Knudsen, Anne (Tidsskriftet Antropologi, 2019)
Kathleen Adler & Marcia Pointon (eds.): The Body Imaged: The Human Form and Visual Culture in the Renaissance Anmeldes af Anne Knudsen